120-year gap: new records of Myrmecophilidae (Orthoptera: Ensifera: Gryllotalpoidea) to Brazil - Pereira-Colavite, Alessandre; Souza, Igor Nascimento De; Lourenço, Aline; Creão-Duarte, Antonio José (Zootaxa, 2025)
A new record of Myrmecophilus (Myrmophilina) americanus Saussure, 1877, in urban areas of Brazil is presented. This is the first record of ant-loving crickets in this region since 1905. Additional records from citizen science data suggest a wider presence of these crickets in Brazil. A distribution map of the records in Brazil and an updated Brazilian key are also included.